Alumni Satisfaction Analysis with UnivQual Theory: Case of Telkom University Class of 2010-2014 - Mahir Pradana; Benny Kurnia; Tri Indra Wijaksana; Fajar Ari Rachdian; Diki Wahyu Nugraha (Forum Inovasi Bisnis dan Manajemen, 2020)
This research was conducted to determine the crucial attributes used by students in choosing universities to enter, in this case choosing to enroll at Telkom University, where the object of this research is the Business Administration students class 2010-2014. The purpose of this study is to explore the factors that are considered by prospective students in making decisions to choose Telkom University campus for study and to find out the dominant factors in choosing the Telkom University campus as a place to study. This research uses a quantitative approach. The scale of the instrument used in this study was the Likert scale. The population in this study were alumni of Telkom University. Tel-U has 45,743 alumni who are members of the Telkom University Alumni Forum (FAST). This study uses a non-probability sampling technique with a purposive sampling type. The data analysis technique used descriptive analysis. It can be concluded that there is no significant effect of the curriculum on improving Telkom University students' skills. We also found a significant effect of facilities and services on improving the skills of Telkom University students. Last we found a significant effect of skill development on Telkom University students' satisfaction.